TECHNOLOGICAL INDICATORS FORMATION OF THE WINTER WHEAT GRAIN QUALITY UNDER THE CONDITIONS OF AGRICULTURE ENVIRONMENTALIZATION OF THE STEPPE OF UKRAINE - Y. Yurkevych; N. Valentiuk; G. Stankevych; А. Kats (Harčova Nauka ì Tehnologìâ, 2023)
Wheat is the leading food grain in the global food balance. Ukraine is among the top 10 world grain producers and therefore the issue of increasing the production of high-quality, environmentally friendly grain is extremely relevant. The aim of the work was to study the influence of the system of agrotechnical measures for the greening of agriculture on the formation of technological indicators of the quality of winter wheat grain, which will make it possible to obtain high-quality environmentally friendly wheat grain in the conditions of the Southern Steppe of Ukraine, as well as reduce the negative pressure on the environment of modern factors of intensification of agriculture. The assessment of the quality of winter wheat grain was carried out according to such technological indicators as the protein content, the quantity and quality of gluten, the falling number, the weight of 1000 grains and bulk density. The experiments were carried out in a grain-rowed short-rotation 5-field crop rotation with alternating crops: peas – winter wheat – corn – sunflower – winter barley. The soil of the experimental plot is southern chernozem, low-humus, medium-thick, difficult loamy in the forest. The conducted studies have shown that the quality of grain changes both from the system of the main soil cultivation in the crop rotation, and from the use of spreaders of by-products of the predecessor, and the influence of these factors manifested itself depending on the weather conditions over the years of research in different ways. The best result with the element of biologization of agriculture was obtained with the use of the biodestructor Cellulad 2 l/ha, which significantly improves the technological indicators of the quality of winter wheat grain. So, on average, over the years of research, the best grain was obtained in the variant with a system of no-till  multi-depth tillage against the background of the introduction of the biodegradable Cellulad 2 l/ha with the protein content of 12.6%, the crude gluten content of 23.4%, the gluten quality indicator according to its deformation index is 82.2 conventional units of the VDC device and the falling number of 334.3 s. With the introduction of additional nitrogen N10 per 1 ton of by-products, as an energy material for the efficient decomposition of organic matter by soil microorganisms, an increase in the quality of winter wheat grain is also observed, but the results are inferior to the best option. Carrying out a moisture-saving system of a non-linear mid-depth basic tillage increases the action of a biodestructor in the conditions of the arid Southern Steppe of Ukraine.